Interest Rate Volatility and the Term Structure: A Two-Factor General Equilibrium Model. - Longstaff, Francis A; Schwartz, Eduardo S (Journal of Finance, 1992)
The authors develop a two-factor general equilibrium model of the term structure. The factors are the short-term interest rate and the volatility of the short-term interest rate. The authors derive closed-form expressions for discount bonds and study the properties of the term structure implied by the model. The dependence of yields on volatility allows the model to capture many observed properties of the term structure. The authors also derive closed-form expressions for discount bond options. The authors use Hansen's generalized method of moments framework to test the cross-sectional restrictions imposed by the model. The tests support the two-factor model.